Analysis of tumor-infiltrating lymphocytes as prognostic factor in triple-negative breast cancer: A protocol of systematic review and meta-analysis - Luciana Carla Martins de Aquino; Elisandra Inara Silva Andrade; Luana Maria Ferreira Nunes; Edilmar de Moura Santos; Ayane Cristine Alves Sarmento; Kleyton Santos de Medeiros; Ana Katherine Gonçalves (PLoS ONE, 2026)
Purpose Breast cancer is the most common malignant tumor among women worldwide, with an estimated 2.3 million new cases and nearly 670,000 deaths reported in 2022. The absence of hormone receptors and HER2 in triple-negative breast cancer (TNBC) reduces therapeutic options, contributing to a poorer prognosis. Tumor-infiltrating lymphocytes (TILs) are cells present in the tumor microenvironment, associated with a better prognosis and potentially playing a role in patient stratification and therapeutic management in the future. This protocol aims to assess the prognostic value of TILs in the survival of patients with TNBC, as well as their relationship with disease recurrence. Methods Comprehensive search will be conducted in the following databases: PubMed, Embase, Lilacs, Web of Science, Scopus, SciELO, ScienceDirect, and the Cochrane Library. The search will include cohort, case-control, and clinical trials studies that approach the prognostic value of TILs in TNBC and their role in optimizing treatment strategies, and no language restrictions. Two independent reviewers will select articles based on predefined inclusion and exclusion criteria, extract data, and assess the risk of bias using the QUIPS tool. Data synthesis will be conducted using the “meta” package in R software, version 4.3.1. Conclusions This systematic review will synthesize current evidence on the prognostic significance of TILs in triple-negative breast cancer and their association with patient survival and disease recurrence. The findings may contribute to a better understanding of TILs as potential biomarkers for prognosis and guide future therapeutic strategies in TNBC management. Review registration: CRD42024568600 .